The use of portable video media vs standard verbal communication in the urological consent process: a multicentre, randomised controlled, crossover trial. (25th August 2016) - Winter, Matthew; Kam, Jonathan; Nalavenkata, Sunny; Hardy, Ellen; Handmer, Marcus; Ainsworth, Hannah; Lee, Wai Gin; Louie‐Johnsun, Mark
Abstract : Objectives: To determine if portable video media (PVM) improves patient's knowledge and satisfaction acquired during the consent process for cystoscopy and insertion of a ureteric stent compared to standard verbal communication (SVC), as informed consent is a crucial component of patient care and PVM is an emerging technology that may help improve the consent process. Patients and Methods: In this multi‐centre randomised controlled crossover trial, patients requiring cystoscopy and stent insertion were recruited from two major teaching hospitals in Australia over a 15‐month period (July 2014–December 2015). Patient information delivery was via PVM and SVC. The PVM consisted of an audio‐visual presentation with cartoon animation presented on an iPad. Patient satisfaction was assessed using the validated Client Satisfaction Questionnaire 8 (CSQ‐8; maximum score 32) and knowledge was tested using a true/false questionnaire (maximum score 28). Questionnaires were completed after first intervention and after crossover. Scores were analysed using the independent samples t ‐test and Wilcoxon signed‐rank test for the crossover analysis. Results: In all, 88 patients were recruited. A significant 3.1 point (15.5%) increase in understanding was demonstrable favouring the use of PVM ( P < 0.001). There was no difference in patient satisfaction between the groups as judged by the CSQ‐8. A significant 3.6 point (17.8%) increase in knowledge score was seen when the SVC group were crossed over to the PVM arm. A total of 80.7% of patients preferred PVM and 19.3% preferred SVC. Limitations include the lack of a validated questionnaire to test knowledge acquired from the interventions. Conclusions: This study demonstrates patients' preference towards PVM in the urological consent process of cystoscopy and ureteric stent insertion. PVM improves patient's understanding compared with SVC and is a more effective means of content delivery to patients in terms of overall preference and knowledge gained during the consent process.